Activity Antidiabetic Of The Ethanol Extract Green Gedi Leaves Medical) On Mice (Mus musculus - Parawansah Parawansah (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2019)
ABSTRACTBackground: Green  gedi leaves  (Abelmoschus manihot (L.)  Medik)  is one plant that has efficacy in treating various diseases one of which is antidiabetic. The nature of the active substance green gedi leaves that capable lower blood glucose levels are flavonoids. Purpose: The purpose of this  study  was  to  determine  the effective  concentration  of  the  extract  of  green  gedi  leaves (Abelmoschus  manihot  (L.)  Medik)  to  lower  the  blood  glucose  levels on  mice  Induced  by Streptozotocin. Method: This type of research is experimental research that consists of 5 treatments with 3 variations dose and 2 controls. The study was conducted by measuring the blo od glucose levels in mice, blood glucose levels after induction to return normal blood glucose levels after oral administration with a suspension of Na. CMC as a control, and the suspension glibenclamid as a comparison with the extract of green gedi leaves concentration of 30 mg/KgBB, 60 mg/KgBB and 90 mg/KgBB with a time of observation for seven days. Result: The data obtained were analyzed using ANOVA and LSD. Conclusion: From this study that the green gedi leaf extract (Abelmoschus manihot (L.) Medik) at a concentration of 90 mg/kgBB is more effectife to give antidiabetic effect with the average reduction in blood glucose levels reach 68,67 mg/dL to mice.Keywords: antidiabetic, abelmoschus manihot (L.) Medik, green gedi leaves, Streptozotocin